Clinical course and treatment of anti-HMGCR antibody–associated necrotizing autoimmune myopathy. Issue 3 (June 2015) - Ramanathan, Sudarshini; Langguth, Daman; Hardy, Todd A.; Garg, Nidhi; Bundell, Chris; Rojana-Udomsart, Arada; Dale, Russell C.; Robertson, Thomas; Mammen, Andrew L.; Reddel, Stephen W.
Abstract : Objective: We examined a cohort of Australian patients with statin exposure who developed a necrotizing autoimmune myopathy (NAM) associated with a novel autoantibody against 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) and describe the clinical and therapeutic challenges of managing these patients and an optimal therapeutic strategy. Methods: Clinical, laboratory, EMG, and histopathologic results and response to immunomodulation are reported in 6 Australian patients with previous statin exposure and antibodies targeting HMGCR. Results: All patients presented with painless proximal weakness following statin therapy, which persisted after statin cessation. Serum creatine kinase (CK) levels ranged from 2, 700 to 16, 200 IU/L. EMG was consistent with a myopathic picture. Muscle biopsies revealed a pauci-immune necrotizing myopathy. Detailed graphical representation of the clinical course of these patients showed a close association with rising CK and an increase in clinical weakness signifying relapses, particularly upon weaning or ceasing steroids. All 6 patients were responsive to initial steroid therapy, with 5 relapsing upon attempts to wean steroids. Both CK and clinical strength improved with the reinstitution of immunotherapy, in particular steroids and IV immunoglobulin (IVIg). All patients required treatment with varying multiagent immunosuppressive regimens to achieve clinical remission, including prednisone (n = 6), IVIg (n = 5), plasmapheresis (n = 2), and additional therapy including methotrexate (n = 6), cyclophosphamide (n = 2), rituximab (n = 2), azathioprine (n = 1), and cyclosporine (n = 1). Conclusions: Recognition of HMGCR antibody–associated NAM is important because these patients are responsive to immunosuppression, and early multiagent therapy and a slow and cautious approach to withdrawing steroids may improve outcomes.